Problems of Investment Literacy and Utilization of Security Crowdfunding in Digital Age Through the Islamic Capital Market - Haanurat, A. Ifayani (Assyfa Journal of Multidisciplinary Education, 2023)
In the rapidly evolving digital age, the Islamic capital market faces significant challenges related to investment literacy and the utilization of security crowdfunding. This study seeks to identify and address these challenges by examining the impact of investment knowledge on the effectiveness of Sharia-compliant security crowdfunding platforms. Through a systematic literature review (SLR) of over 50 studies across multiple regions, we focus on individual investors participating in the Islamic capital markets. Our analysis reveals a pervasive gap in investment literacy, with 65% of potential investors lacking a fundamental understanding of financial principles, risk management, and Sharia-compliant investment specifics. This deficiency critically impedes the optimal use of security crowdfunding platforms. Furthermore, the study highlights the increasing reliance on digital platforms, underscoring the urgent need for targeted educational programs and enhanced regulatory frameworks. We propose developing comprehensive educational initiatives centered on Islamic finance principles and bolstering regulatory support to promote informed and inclusive participation in the Islamic financial ecosystem. Our findings suggest that such initiatives could improve investment literacy by up to 40%, enabling more effective engagement with digital investment platforms. Additionally, we recommend that future research delve into demographic factors affecting investment literacy and assess the efficacy of different educational programs. By addressing these issues, the Islamic capital market can better harness the potential of security crowdfunding in the digital era, ultimately fostering growth and inclusivity.